Предмет: Алгебра,
автор: kornevasnezana2
(x+1)^3-x^2(x+3)+2=0
Ответы
Автор ответа:
1
X^3+3x^2+3x+1-x^3-3x^2+2=0
3x+3=0
3x=-3
X=-1
Автор ответа:
1
(X+1)^3-x^2(x+3)+2=0;
X^3+3x+1-x^3+3x^3+2=0;
3x+3=0;
3x=0-3;
3x=-3;
X=-3:3;
X=-1
Ответ:-1
X^3+3x+1-x^3+3x^3+2=0;
3x+3=0;
3x=0-3;
3x=-3;
X=-3:3;
X=-1
Ответ:-1
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Физика,
автор: vikaigogo2019
Предмет: Математика,
автор: d65bcvs6cn
Предмет: Литература,
автор: artemklimov64
Предмет: Алгебра,
автор: mankoanna2016